Is it necessary to warm infants' feeds?. Issue 11 (November 1979) - Costalos, C; Ross, I; Campbell, A G; Sofi, M
Abstract : The effect of temperature on gastric emptying after milk feeds was studied in 31 newborn infants. Test meals were a commercially prepared modified cows' milk (a) at body temperature and (b) at room temperature. Our results suggest that temperature has no effect on gastric emptying.